2013
DOI: 10.1161/circresaha.113.301283
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Stem Cell–Derived CD166 + Precursors Develop Into Fully Functional Sinoatrial-Like Cells

Abstract: Rationale: A cell-based biological pacemaker is based on the differentiation of stem cells and the selection of a population displaying the molecular and functional properties of native sinoatrial node (SAN) cardiomyocytes. So far, such selection has been hampered by the lack of proper markers. CD166 is specifically but transiently expressed in the mouse heart tube and sinus venosus, the prospective SAN. Objective:We have explored the possibility of using CD166 expression for isolating SAN progenitors from dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 54 publications
(63 reference statements)
7
57
0
Order By: Relevance
“…[46][47][48][49] However, their clinical use is overshadowed by the occurrence of serious cardiac arrhythmias in the transplanted animals, likely because of poor electromechanical coupling of the injected cells with the host cells. 50 Moreover, the use of induced pluripotent stem cell-derived cardiac myocytes for cardiac repair is hampered by their immature phenotype and the presence of epigenetic and genetic changes.…”
Section: E72mentioning
confidence: 99%
“…[46][47][48][49] However, their clinical use is overshadowed by the occurrence of serious cardiac arrhythmias in the transplanted animals, likely because of poor electromechanical coupling of the injected cells with the host cells. 50 Moreover, the use of induced pluripotent stem cell-derived cardiac myocytes for cardiac repair is hampered by their immature phenotype and the presence of epigenetic and genetic changes.…”
Section: E72mentioning
confidence: 99%
“…In 2006, Hirata and coworkers showed that expression of CD166, an adhesion molecule also called activated leukocyte cell adhesion (ALCAM or DS-GRASP), marked the tubular heart and the sinus venosus at an early stage of development (E8.5), whereas its expression broadened to other organs at later stages (Hirata et al, 2006). We recently demonstrated that in mice, during cardiac development at E10.5, CD166 expression almost completely overlaps with that of HCN4; at later stages of differentiation (E12.5), HCN4 and CD166 still colocalize in the SAN region, but CD166 expression widens also to other cardiac regions and to extracardiac organs as well (Scavone et al, 2013). These data indicate that, within a well defined developmental window, CD166 can indeed identify pacemaker cells, in particular SAN precursors, even though it is not strictly a cardiac marker.…”
Section: B Sinoatrial Precursormentioning
confidence: 93%
“…The primary source of the Ca 2+ released from the SR and removed by the Na/Ca exchange current is the L-type 370 Ca current, I CaL , which is largely responsible for the action potential upstroke in SAN cells. In this respect, other potential identifying characteristics of the SAN cell are a high abundance of the L-type calcium channel isoform Ca V 1.3 and T-type isoforms Ca V 3.1 and Ca V 3.2 (Mangoni et al, 2003;Marionneau et al, 2005;Chandler et al, 2009;Scavone et al, 2013) and also the relative absence of fast inward Na (Na V 1.5) current, although the latter is not absolute; several studies have reported the presence of Na current and Na channel isoforms in SAN, depending on species and developmental stage (Baruscotti et al, 1996(Baruscotti et al, , 1997Maier et al, 2003).…”
Section: The Adult Sinoatrial Nodementioning
confidence: 99%
See 1 more Smart Citation
“…Initial attempts were directed at producing functional SAN cells from these stem cells. It was shown that it is possible to use CD 166 expression to select SAN precursor cells [20]. However, attempts to autologously graft the SAN or inject the myocytes failed to provide sustained biological pacemaker activity [21,22].…”
Section: Cell-based Approachmentioning
confidence: 99%